Emerging Roles of Ubiquitin-Specific Protease 25 in Diseases - Zhu, Wenjing; Zheng, Dandan; Wang, Dandan; Yang, Lehe; Zhao, Chengguang; Huang, Xiaoying (Frontiers in Cell and Developmental Biology, 2021)
The balance of ubiquitination and deubiquitination plays diverse roles in regulating protein stability and cellular homeostasis. Deubiquitinating enzymes catalyze the hydrolysis and removal of ubiquitin chains from target proteins and play critical roles in various disease processes, including cancer, immune responses to viral infections and neurodegeneration. This article aims to summarize roles of the deubiquitinating enzyme ubiquitin-specific protease 25 (USP25) in disease onset and progression. Previous studies have focused on the role of USP25 in antiviral immunity and neurodegenerative diseases. Recently, however, as the structural similarities and differences between USP25 and its homolog USP28 have become clear, mechanisms of action of USP25 in cancer and other diseases have been gradually revealed.